2020
DOI: 10.1186/s12882-020-01978-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes of kidney transplant recipients undergoing non-transplant-related elective surgery: a systematic review and meta-analysis

Abstract: Background: Reliable estimates of the absolute and relative risks of postoperative complications in kidney transplant recipients undergoing elective surgery are needed to inform clinical practice. This systematic review and meta-analysis aimed to estimate the odds of both fatal and non-fatal postoperative outcomes in kidney transplant recipients following elective surgery compared to non-transplanted patients. Methods: Systematic searches were performed through Embase and MEDLINE databases to identify relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…The present study proved that AKI occurred more commonly in the KT group than in the nontransplantation group even though NSAIDS were not used. A recent systematic review noted that the odds of postoperative AKI were higher in kidney transplant patients than in the nontransplantation group, and the odds were highest after orthopedic surgery, being 15.26 30 . Choi et al 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study proved that AKI occurred more commonly in the KT group than in the nontransplantation group even though NSAIDS were not used. A recent systematic review noted that the odds of postoperative AKI were higher in kidney transplant patients than in the nontransplantation group, and the odds were highest after orthopedic surgery, being 15.26 30 . Choi et al 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review noted that the odds of postoperative AKI were higher in kidney transplant patients than in the nontransplantation group, and the odds were highest after orthopedic surgery, being 15.26. 30 Choi et al 31 identified that solid organ transplantation was an independent predictor of postoperative AKI in patients undergoing total hip arthroplasty due to avascular necrosis of femoral head. The incidence of AKI in the present study was higher than that in the previous study (39.1% vs. 28.8%).…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that disease type 4 (after renal transplant) had a shorter waiting time for admission than other disease types. This is because in patients with a after renal transplant, taking immunosuppressants leads to a decrease in immunity, resulting in rapid progression of infections and other complications, and an increased probability of systemic damage [ 41 , 42 ]. Lengthy waiting times will seriously endanger their life, so the waiting time is shorter than those of other disease types.…”
Section: Discussionmentioning
confidence: 99%
“…Bei geplanten Herzoperationen ist ein HbA 1c -Wert unter 7 % bei Menschen mit Diabetes mit einer erniedrigten Inzidenz einer akuten Nierenschädigung assoziiert [ 3 ]. Nierentransplantierte mit Diabetes mellitus Typ 2 haben bei geplanten operativen Eingriffen insgesamt ein erhöhtes Risiko, insbesondere auch für ein akutes Nierenversagen [ 16 ].…”
Section: Risiken Für Eine Akute Nierenschädigungunclassified